Digital Service Innovation and Customer Value - Deryana, Lilian; Hadady, Hartaty; Jabid, Abdullah W.; Sirat, Abdul Hadi (International Journal of Business, Law, and Education, 2023)
The limited research linking digital service innovation to the small business context makes this research mandatory. This research itself examines the impact resulting from digital service innovation on customer value in Ternate City. A total of 113 respondents were involved in this study. The data in this study were collected through a survey with a questionnaire. Testing the research hypothesis was carried out using simple linear regression analysis using SPSS version 24. The results revealed that there was a positive relationship between digital service innovation and customer value. Next, recommendations for future research are discussed.